Optimization of process conditions for extraction of xanthine oxidase inhibitor form potential Malaysian medicinal plant - Jamal, Parveen; Amid, Azura (s.n, 2012)
Xanthine oxidase (XO) is an enzyme involved in the formation of uric acid in the body by catalyzing the oxidation of hypoxanthine to xanthine, and then, xanthine to uric acid. Excess serum accumulated with uric acid can lead to a type of arthritis known as gout. Hence, introducing natural xanthine oxidase inhibitor (XOI) as new source of gout medication is highly granted. The leaves of five local medicinal plants were examined for the inhibition of XO under four process conditions, namely, extraction temperature, extraction time, agitation speed, and ratio of the sample to the solvent. Distilled water and 70% methanol were employed in the extraction process. The degree of inhibition was determined by measuring the absorbance spectrophotometrically at 290 nm associated with uric acid formation. Aqueous-methanolic extract of Morinda elliptica leaves was found to have the highest XO inhibitory activity at 100 μg/ml with 86.94 ± 0.34%, thus selected for optimization of process conditions for extraction by using Central Composite Design (CCD) from Design Expert v.6.0.8. The second highest was aqueous-methanolic extract of Mentha spicata leaves with 86.49 ± 0.84% followed by aqueous-methanolic extract of Carica papaya leaves with 79.28 ± 0.29%. Development of process conditions for extraction of XOI from leaves of Morinda elliptica was performed and the analysis of variance demonstrated that the model F-value of 18.31 showed the significance of the model with R2 of 97.71%. The analysis revealed that the XO inhibitory activity was enhanced to 88.93%, reached at 32 ºC, 30 h, 125 rpm and 1 g/15 ml of solvent. The results were encouraging to formulate food or nutraceutical products incorporating natural XOI, an alternative to irresponsive synthetic XOI.